Short ROSE-Like RNA Thermometers Control IbpA Synthesis in Pseudomonas Species - Krajewski, Stefanie S.; Nagel, Miriam; Narberhaus, Franz (PLOS ONE, 2013)
The bacterial small heat shock protein IbpA protects client proteins from aggregation. Due to redundancy in the cellular chaperone network, deletion of the ibpA gene often leads to only a mild or no phenotypic defect. In this study, we show that a Pseudomonas putida ibpA deletion mutant has a severe growth defect under heat stress conditions and reduced survival during recovery revealing a critical role of IbpA in heat tolerance. Transcription of the ibpA gene depends on the alternative heat shock sigma factor σ32. Production of IbpA protein only at heat shock temperatures suggested additional translational control. We conducted a comprehensive structural and functional analysis of the 5′ untranslated regions of the ibpA genes from P. putida and Pseudomonas aeruginosa. Both contain a ROSE-type RNA thermometer that is substantially shorter and simpler than previously reported ROSE elements. Comprised of two hairpin structures only, they inhibit translation at low temperature and permit translation initiation after a temperature upshift. Both elements regulate reporter gene expression in Escherichia coli and ribosome binding in vitro in a temperature-dependent manner. Structure probing revealed local melting of the second hairpin whereas the first hairpin remained unaffected. High sequence and structure conservation of pseudomonal ibpA untranslated regions and their ability to confer thermoregulation in vivo suggest that short ROSE-like thermometers are commonly used to control IbpA synthesis in Pseudomonas species.